STUDI ANALISIS PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, DAN TRANSENDENTAL TERHADAP KINERJA PEGAWAI DI POLITEKNIK API YOGYAKARTA - Tri Wahyudi; Siti Fatimah; Erwin Budi Setyawan (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2026)
This study examines the influence of Intellectual Intelligence (IQ), Emotional Intelligence (EQ), and Spiritual Intelligence (SQ) on employee performance at the API Yogyakarta Polytechnic amidst the challenges of vocational education that demands technological adaptability and strong moral integrity. A quantitative approach was used using multiple linear regression analysis. Data were collected through questionnaires distributed to 41 respondents who were all employees of the “API” Yogyakarta Polytechnic. The analysis included classical assumption tests, namely normality, heteroscedasticity, and multicollinearity tests, as well as hypothesis testing using t-tests and F-tests with SPSS version 28.0. The results showed that IQ, EQ, and SQ simultaneously had a significant influence on employee performance, contributing 45.8% based on the Adjusted R Square value. Partially, IQ and SQ were found to have a positive and significant influence on performance because they support technical competence, discipline, and work ethics. In contrast, EQ did not show a significant independent influence in the polytechnic work environment, which is highly oriented towards rigid Standard Operating Procedures (SOPs) and objective data processing. High emotional sensitivity is thought to potentially increase subjectivity and emotional burnout. This study concluded that a strong combination of IQ and SQ creates employees who are technically competent and possess high integrity. Management is advised to strengthen integrity-based recruitment and redesign performance indicators to optimize the role of emotional intelligence in the future.